Positioned numerical semigroups - Branco, M. B. (2020)
A numerical semigroup S is positioned if for all s ∈ N\S we have that F(S) + m(S) − s ∈ S. In this paper, we give algorithms to compute the set of positioned semigroups and a criterium to check whether S is or not is positioned. Furthermore, we prove the Wilf’s conjecture for this type of numerical semigroups.